The lost revolution : the story of the Official IRA and the Workers' Party - Hanley, Brian; Millar, Scott (Dublin : Penguin, 2009)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: marxisten; Noord-Ierland.